To simplify the expression \( \sqrt{8} - \sqrt{32} \), we start by simplifying each square root.
-
Simplifying \( \sqrt{8} \): \[ \sqrt{8} = \sqrt{4 \times 2} = \sqrt{4} \cdot \sqrt{2} = 2\sqrt{2} \]
-
Simplifying \( \sqrt{32} \): \[ \sqrt{32} = \sqrt{16 \times 2} = \sqrt{16} \cdot \sqrt{2} = 4\sqrt{2} \]
Now substitute the simplified forms back into the expression: \[ \sqrt{8} - \sqrt{32} = 2\sqrt{2} - 4\sqrt{2} \]
- Combine like terms: \[ 2\sqrt{2} - 4\sqrt{2} = (2 - 4)\sqrt{2} = -2\sqrt{2} \]
Thus, the simplified expression is: \[ \boxed{-2\sqrt{2}} \]